Trauma Pasca Bencana dan Tantangan Intervensi Psikososial: Kajian Terhadap Respons Psikologis di Gunung Semeru - Akbar, Ahmad Aldizar; Rahmat, Hayatul Khairul; Wahyuningtyas, Ayu (Trends in Applied Sciences, Social Science, and Education, 2025)
The eruption of Mount Semeru in December 2021 had multidimensional impacts on affected communities, not only physically and economically but also psychologically. This article aims to examine various psychosocial intervention approaches for disaster survivors, particularly children and other vulnerable groups, in the aftermath of the eruption. This study employs a literature review method, analyzing nine national journal articles selected based on their relevance to the topic and intervention strategies. The findings indicate that methods such as trauma healing, play therapy, Psychological First Aid (PFA), and mental health nursing interventions are effective in reducing trauma symptoms and improving the psychological well-being of survivors. Participatory and community-based approaches, such as Asset-Based Community Development (ABCD) and Participatory Learning and Action (PLA), have shown more sustainable and contextually relevant outcomes. This study concludes that strengthening holistic and locally driven psychosocial interventions is essential in post-disaster recovery strategies.